The impact of entrepreneurial passions on organizational commitment in SMEs: the mediating role of perceived organizational support / Md Sharif Md Said - Md Said, Md Sharif (2016)
This study examines a model involving Entrepreneurial Passion (EP), Perceived Organizational Support (POS), and Organizational Commitment (OC). It was hypothesized that employees' EP will be positively related to their organizational commitment, and that perceived organizational support would serve as a mediator in the relationship between employees' perceived EP and employees' OC. Data were gathered using cluster sampling method from a sampling frame of 231 Malaysian Manufacturing Related Small and Medium Enterprises (SMEs) located within the Klang Valley comprising the States of Selangor and Federal Territory of Kuala Lumpur. Confirmatory Factor Analysis (CFA) was performed on the 258 samples using structural equation modeling. The CFA revealed that there is a positive and direct relationship between EP and OC as propounded by earlier authors. The CFA also demonstrated that POS has a direct, positive and significant relationship with OC as hasbeen established by earlier researches. Upon introducing Perceived Organizational Support as a mediating variable it was found that POS completely mediates the relationship between EP and OC. EP was also found to be directly, positively and significantly related to POS. With these findings the theoretical and managerial implications of this study are suggested. Earlier studies on EP and the impact on OC were conducted in the Western setting in particular the United States but this study is conducted in "eastern" environment specifically in Malaysia.